Identifying undiagnosed HIV in men who have sex with men (MSM) by offering HIV home sampling via online gay social media: a service evaluation. (24th May 2016) - Elliot, E; Rossi, M; McCormack, S; McOwan, A
Abstract : Background: An estimated one in eight men who have sex with men (MSM) in London lives with HIV, of which 16% are undiagnosed. It is a public health priority to minimise time spent undiagnosed and reduce morbidity, mortality and onward HIV transmission. 'Dean Street at Home' provided an online HIV risk self-assessment and postal home HIV sampling service aimed at hard-to-reach, high-risk MSM. Objectives: This 2-year service evaluation aims to determine the HIV risk behaviour of users, the uptake of offer of home sampling and the acceptability of the service. Methods: Users were invited to assess their HIV risk anonymously through messages or promotional banners on several gay social networking websites. Regardless of risk, they were offered a free postal HIV oral fluid or blood self-sampling kit. Reactive results were confirmed in clinic. A user survey was sent to first year respondents. Results: 17 361 respondents completed the risk self-assessment. Of these, half had an 'identifiable risk' for HIV and a third was previously untested. 5696 test kits were returned. 121 individuals had a reactive sample; 82 (1.4% of returned samples) confirmed as new HIV diagnoses linked to care; 14 (0.25%) already knew their diagnosis; and 14 (0.25%) were false reactives. The median age at diagnosis was 38; median CD4 505 cells/µL and 20% were recent infections. 61/82 (78%) were confirmed on treatment at the time of writing. The post-test email survey revealed a high service acceptability rate. Conclusions: The service was the first of its kind in the UK. This evaluation provides evidence to inform the potential roll-out of further online strategies to enhance community HIV testing.